2017
DOI: 10.1021/jacs.7b01269
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of Endogenous Palmitic Acid Ester of 9-Hydroxystearic Acid and Relevance of Absolute Configuration to Regulation

Abstract: Lipids have fundamental roles in the structure, energetics, and signaling of cells and organisms. The recent discovery of fatty acid esters of hydroxy fatty acids (FAHFAs), lipids with potent anti-diabetic and anti-inflammatory activities, indicates that our understanding of the composition of lipidome and the function of lipids is incomplete. The ability to synthesize and test FAHFAs was critical in elucidating the roles of these lipids, but these studies were performed with racemic mixtures, and the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 22 publications
2
79
0
Order By: Relevance
“…ELISA kits were obtained from Crystal Chem (mouse insulin) and Alpco Diagnostics (human insulin). Both 5-and 9-PAHSAs were synthesized on the basis of established methods (67). MIN6 cells were obtained from the American Type Culture Collection (ATCC).…”
Section: Discussionmentioning
confidence: 99%
“…ELISA kits were obtained from Crystal Chem (mouse insulin) and Alpco Diagnostics (human insulin). Both 5-and 9-PAHSAs were synthesized on the basis of established methods (67). MIN6 cells were obtained from the American Type Culture Collection (ATCC).…”
Section: Discussionmentioning
confidence: 99%
“…In that context, the preparation of synthetic FAHFAs as their racemic form was sufficient. However, for a better understanding of their biosynthesis and their mechanisms of action(s) it is more appropriate to perform biological experiments with optically pure FAHFAs …”
Section: Fahfas Are Endogenous Lipidsmentioning
confidence: 99%
“…However,f or ab etter understanding of their biosynthesis and their mechanisms of action(s) it is more appropriate to perform biological experiments with optically pure FAHFAs. [5,31] Nelson et al [31] recently reported the synthesis of enantiomericallye nriched 9-PAHSAs.T hey secured the desired alcohol configurations by using ac hiral pool strategy (Scheme 9). Thus, optically pure (S)-epichlorhydrin was subjected to copper-mediated chemo-and regioselective ring-opening with the Grignard reagent 13 prepared from 8-bromo-1-octene followed by alkaline-induced epoxide formation.T he newly formed epoxide 14 was then ring-opened with n-octyl magnesium chloride to the desired enantioenriched secondary alcohol 15 at positionC 10 in aC 19 carbon chain length.…”
Section: Synthesis Of Optically Active Fahfasmentioning
confidence: 99%
“…These products, like 9 -HSA, can act as endogenous intermediate modulators allowing RPC to initiate differentiation during retinal development and later in the maintenance of tissue homeostasis in the adult retina. In addition to this new role in the retina, other work on derivatives of the lipid such as fatty acid esters and in particular palmitic acid esters of 9 -HSA ( 9 -PAHSA) demonstrated their in anti-diabetic and antiinflammatory properties, extending its role to another range of biological activities (Yore et al , 2014; Lee et al , 2016; Nelson et al , 2017). Our study provides insights in the mechanism of action of 9 -HSA in vivo via its inhibitory activity on HDAC1 and proposes a novel mechanism linking H 2 O 2 homeostasis and neuronal differentiation via the modulation of lipid peroxidation that leads to the expression of key neuronal genes required for the switch from proliferation to differentiation of RPCs (Fig.…”
Section: Discussionmentioning
confidence: 99%